Variation of fundamental parameters and dark energy: a principal component approach - Amendola, Luca (Arxiv, 2012)
We discuss methods based on Principal Component Analysis to constrain the dark energy equation of state using a combination of Type Ia supernovae at low redshift and spectroscopic measurements of varying fundamental couplings at higher redshifts. We discuss the performance of this method when future better-quality datasets are available, focusing on two forthcoming ESO spectrographs - ESPRESSO for the VLT and CODEX for the E-ELT - which include these measurements as a key part of their science cases. These can realize the prospect of a detailed characterization of dark energy properties almost all the way up to redshift 4.